Nocturnal periodic breathing and the development of acute high altitude illness. - Eichenberger, Urs; Weiss, E.; Riemann, D.; Oelz, Oswald; Bärtsch, Peter (American journal of respiratory and critical care medicine, 1996)
We tested the hypothesis that periodic breathing (PB) at high altitude is more frequent and arterial oxygen desaturation more severe during sleep in subjects developing high altitude pulmonary edema (HAPE) or acute mountain sickness (AMS) compared with subjects remaining healthy. We registered thoraco-abdominal movement, electro-encephalogram and oxygen saturation by pulse oximeter (pSao2) in 21 subjects during the first night spent at the altitude of 4,559 m. During the subsequent stay at 4,559 m, eight subjects remained well (controls), five subjects developed AMS and eight subjects developed HAPE. PB was found in all sleep stages and the percentage PB in any sleep stage was not significantly different between groups. There was a trend towards more PB in the HAPE vs. AMS and control group lasting 80 +/- 5 (mean +/- SE), 58 +/- 7, 57 +/- 9% of analyzable time, respectively (p = 0.09). The mean nocturnal decrease of pSao2 for these groups was 8.7 +/- 1.9, 5.4 +/- 2.1, 4.8 +/- 1.2%; (p = 0.36) and the median nocturnal pSao2 was 49 +/- 3, 63 +/- 3, and 63 +/- 4% (p = 0.02). Arterial blood gas analysis before and after sleep recordings indicate that the significantly lower Sao2 in the HAPE group is secondary to gas exchange rather than ventilation. The nocturnal decrease of pSao2 did not correlate with the time of PB nor the number of desaturation events > or = 4%. These findings suggest that more frequent PB in the HAPE group is a consequence of lower Sao2 due to impairment of gas exchange.